microRNAs: An Emerging Paradigm in Lung Cancer Chemoresistance - Naidu, Srivatsava; Garofalo, Michela (Frontiers in Medicine, 2015)
Lung cancer is considered as deadly of all cancers with limited therapeutic options. Although advanced drugs have been tried in clinic, the therapeutic success has largely been hampered due to rapid development of drug resistance mechanisms. Recently, microRNAs (miRNAs), a class of small non-coding RNAs have occupied centre stage in cancer biology. MiRNAs negatively regulate gene expression either by promoting degradation or interfering with translation of messenger RNA targets. Several lines of evidence have confirmed the crucial role of miRNAs in carcinogenesis, and, importantly, in the acquisition of resistance to chemotherapeutics. Modulation of miRNA expression levels has been proven to increase the efficacy of genotoxic drugs in various preclinical cancer studies. Therefore, comprehensive understanding of the role(s) of these key players in drug resistance may provide novel opportunities to design effective combinatorial therapeutic strategies for cancer treatment. In this review, we highlight recent findings on miRNAs acting as oncomiRs and tumour suppressor genes in lung cancer. Moreover, we discuss the involvement of microRNAs in different mechanisms of drug resistance in this deadly disease.